Species composition and ecology of naked amoebae in Ukraine and adjacent territories - Patsyuk , M.K. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2025)
From the fresh and marine waters we identified 56 species of naked amoebae. Among the identified species, 17 were found to be the most frequent in Ukrainian water bodies, 27 species were infrequent, and 12 showed intermediate frequency of occurrence. Were determined the ecological groups of species to abiotic factors of the aquatic environment. Eurythermal: Thecamoeba striata, Thecamoeba sp., Mayorella cantabrigiensis, Korotnevella stella, Vannella lata, Vannella sp., Acanthamoeba sp., Cochliopodium actinophorum. Stenothermal thermophilic: Deuteramoeba mycophaga, Thecamoeba quadrilineata, Stenamoeba stenopodia, Vexillifera bacillipedes, Ripella sp., Willaertia magna. Stenothermal psychrophilic: Saccamoeba sp. (3). Euryoxidic: Rhizamoeba sp. (1), Rhizamoeba sp. (2), Deuteramoeba mycophaga, Saccamoeba stagnicola, Saccamoeba wakulla, Saccamoeba sp. (1), Saccamoeba sp. (3), Thecamoeba striata, Thecamoeba quadrilineata, Thecamoeba verrucosa, Thecamoeba terricola, Thecamoeba sp., Stenamoeba stenopodia, Paradermamoeba valamo, Paradermamoeba levis, Mayorella cantabrigiensis, Mayorella vespertilioides, Mayorella penardi, Mayorella sp. (2), Korotnevella stella, Vexillifera bacillipedes, Ripella platypodia, Ripella sp., Vannella lata, Vannella sp., Acanthamoeba sp., Pellita digitata, Cochliopodium actinophorum, Flamella sp., Vahlkampfia sp. (1), Vahlkampfia sp. (3), Vahlkampfia avara, Willaertia magna. Stenooxidic: Amoeba proteus, Polychaos dubium, Saccamoeba limax, Saccamoeba sp. (2), Thecamoeba sphaeronucleolus, Thecamoeba similis, Mayorella viridis, Mayorella sp. (1), Korotnevella diskophora, Cochliopodium minus, Vahlkampfia sp. (2). Broad-tolerant to dissolved organic matter: Rhizamoeba sp. (1), Deuteramoeba mycophaga, Saccamoeba stagnicola, Thecamoeba striata, Thecamoeba quadrilineata, Thecamoeba sp., Stenamoeba stenopodia, Paradermamoeba valamo, Paradermamoeba levis, Mayorella cantabrigiensis, Mayorella vespertilioides, Korotnevella stella, Korotnevella diskophora, Vexillifera bacillipedes, Ripella platypodia, Ripella sp., Vannella lata, Vannella sp., Acanthamoeba sp., Cochliopodium actinophorum, Vahlkampfia avara, Vahlkampfia sp. (1), Vahlkampfia sp. (2), Vahlkampfia sp. (3). Narrow-tolerant to dissolved organic matter: Rhizamoeba sp. (2), Amoeba proteus, Polychaos dubium, Saccamoeba wakulla, Saccamoeba sp. (1), Saccamoeba sp. (2), Thecamoeba sphaeronucleolus, Thecamoeba terricola, Mayorella viridis, Mayorella sp. (1), Pellita digitata, Cochliopodium minus, Flamella sp. Stenobionts in relation to dissolved organic matter in water: Saccamoeba limax, Saccamoeba sp. (3), Thecamoeba verrucosa, Thecamoeba similis, Mayorella penardi, Mayorella sp. (2), Willaertia magna. Euryhaline: Acanthamoeba griffini, Vannella simplex. Stenohaline: Saccamoeba marina, Vexillifera armata, Vannella devonica, Vannella aberdonica, Vannella plurinucleolus, Cochliopodium gulosum, Mayorella gemmifera, Thecamoeba orbis, Thecamoeba hilla, Stenamoeba sp.